The Role of Trust, Ease of Use and Security on Shopping Interests at Lazada - Misbachul Munir; Didit Darmawan (Engineering and Technology International Journal, 2022)
Online shopping behavior has been widely observed by various studies. This led to continuous theory development. Online sellers have developed forms and are increasingly attracting online shopping enthusiasts. Various factors can cause the emergence of interest in shopping online. This study intends to observe the variables of trust, ease of use and security on shopping interest in the well-known marketplace, namely Lazada. This study took a sample of 100 people as Lazada users. With the regression technique it is known that trust is a variable that plays a significant role in shopping interest at Lazada. The same goes for ease of use and security.